1997
DOI: 10.1051/aas:1997249
|View full text |Cite
|
Sign up to set email alerts
|

Morphological classification and structural parameters of galaxies in the Coma and Perseus clusters

Abstract: Abstract. We present the results of an isophotal shape analysis of galaxies in the Coma and Perseus clusters. These data, together with those of two previous papers, provide two complete samples of galaxies with reliable Hubble types in rich clusters:1) all galaxies brighter than m b = 16.5 falling within one degree (= 2.3 Mpc) from the center of the Coma cluster (187 galaxies),2) all galaxies brighter than m Zwicky = 15.7 in a region of 5• 3 ×5• 27 around the center of the Perseus cluster (139 galaxies).These… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(109 citation statements)
references
References 6 publications
11
96
2
Order By: Relevance
“…Considering first the structure and morphology of the cluster members, we found some evidence for a lack of quiescent disk-like galaxies relative to the field population. In the context of cluster studies at lower redshift, this is consistent with the idea that the cluster ellipticals are formed early (z > 2) in dissipative mergers, probably continuing to evolve via dry mergers, whereas many S0's are formed much later at z 0.5 and decline in numbers toward higher redshifts (e.g., Dressler et al 1997;Andreon et al 1997;Smith et al 2005;Postman et al 2005;Poggianti et al 2009). An interesting related development is the observation that the fraction of quiescent galaxies in the field with disklike components appears to increase at z > 1, particular among massive (M * > 10 11 M ) systems (see references in Section 6.2).…”
Section: Discussionsupporting
confidence: 82%
“…Considering first the structure and morphology of the cluster members, we found some evidence for a lack of quiescent disk-like galaxies relative to the field population. In the context of cluster studies at lower redshift, this is consistent with the idea that the cluster ellipticals are formed early (z > 2) in dissipative mergers, probably continuing to evolve via dry mergers, whereas many S0's are formed much later at z 0.5 and decline in numbers toward higher redshifts (e.g., Dressler et al 1997;Andreon et al 1997;Smith et al 2005;Postman et al 2005;Poggianti et al 2009). An interesting related development is the observation that the fraction of quiescent galaxies in the field with disklike components appears to increase at z > 1, particular among massive (M * > 10 11 M ) systems (see references in Section 6.2).…”
Section: Discussionsupporting
confidence: 82%
“…The stripping of the interstellar medium causes a decrease of the star formation rate, with a subsequent increase of the post starburst galaxy fraction. 6) Andreon et al (1997) found that early-type galaxies in CL 0939+4713 do not show a radial symmetry, but are distributed along a privileged direction. This direction roughly coincides with the X-ray major axis and therefore with the possible collision axis.…”
Section: Discussion Of the Merger Hypothesismentioning
confidence: 99%
“…Spectroscopic redshifts for almost all galaxies of interest are available in Treu et al (2015) and Ebeling et al (2014), making the photo-z pre-selection necessary only for excluding a few galaxies without a spectroscopic redshift but with a SED pointing toward a manifestly different redshift. Similarly, the passive pre-selection is in principle unnecessary because all non-passive galaxies are clearly A2, page 3 of 17 A&A 593, A2 (2016) Andreon et al (1996Andreon et al ( , 1997; numbers in boldface identify the band used for the isophotal analysis.…”
Section: Z < 1 Clustersmentioning
confidence: 99%
“…Abell 1656 (Coma) galaxies use ground-based V-or r-band observations, typically 20 min long with <1.2 arcsec seeing at a 2 m telescope (from Andreon et al 1996Andreon et al , 1997. Effective radii, derived as in this work and using the same software, are available in the references mentioned.…”
Section: Z < 1 Clustersmentioning
confidence: 99%